Petrological and geochemical insights into the magma plumbing system of the Daliuchong dacite eruption, Tengchong Volcanic Field, SW China - Su, Chaoxing; Wang, Meng; Luo, Diao; Hou, Tong (Frontiers in Earth Science, 2024)
Daliuchong volcano is the result of one of the largest eruptive events within the Tengchong Volcanic Field (TVF) during the Early-Middle Pleistocene. The Daliuchong pyroclastic rocks are dacitic in composition. The samples show porphyritic textures, characterized by phenocrysts of plagioclase, amphibole, clinopyroxene, orthopyroxene, and Fe-Ti oxides. Additionally, two distinct types of glomerocrysts are identified: gabbroic glomerocryst containing plagioclase + clinopyroxene + orthopyroxene ± Fe-Ti oxides assemblage, and dioritic glomerocrysts containing plagioclase + amphibole ± pyroxene ± Fe-Ti oxides assemblage. The Daliuchong dacite exhibits bulk compositional heterogeneity. Analysis of bulk-rock data suggests that this heterogeneity may arise from both the differentiation of the dacite itself and the injection of mafic magma. Drawing upon similarities in composition between the Daliuchong dacite and experimentally-produced partial melts of metamorphic basalt, we propose that the Daliuchong dacite was predominantly formed through the partial melting of the mafic lower crust. Crystallization pressure and temperature estimates for clinopyroxene range from 6.0 to 8.7 kbar and 918 to 972 ℃, respectively. However, two phenocrystic clinopyroxenes exhibit P-T conditions of 2.2 kbar and 886°C, and 3.0 kbar and 897°C.Additionally, amphibole geothermobarometry calculations indicate P-T-fO 2 -H 2 O melt conditions ranging from 1.8 to 2.6 kbar, 824 to 900℃, ΔNNO +1.5 to +4.4, and 4.9 to 6.7 wt.%, respectively. Based on the observed phase relations and the calculated crystallization conditions, we propose that during the differentiation of the Daliuchong dacite, dacitic magma accumulated in a deep magma chamber (21-32 km) before subsequently ascending towards shallower depths. Crystallization of plagioclase, amphibole, Fe-Ti oxides, and small amounts of pyroxene and apatite occurred at a shallower depth (7-10 km). The presence of coarse-sieve texture, fine-sieve texture, and oscillatory zoning with high amplitude in plagioclase suggests intermittent injection of mafic magma into the shallow magma chamber, with the eruption of dacitic magma occurring after the final mafic magma replenishment.